Parents Attention Affect to Students Learning Discipline: Case Study of Class XI IPA Students of SMA Hang Tuah 4 Surabaya - Endrayana Putut Laksminto Emanuel; Radhitya Duta Pradana; Fatkul Anam; Wahyuningtyas Puspitorini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
One reliable measure of students' learning success is their level of learning discipline. One factor influencing students' learning discipline is parental attentiveness. This study aims to determine the relationship between students' learning discipline and parents' attentiveness. This study use quantitative methods that involve correlation. Basic random sampling and probability sampling techniques were combined by the researchers. The sample consisted of 30 individuals, while the population consisted of 150 individuals. Data was gathered by questionnaires, interviews, and documentation. The data analysis's findings show a connection between parental attention and the learning discipline of class XI IPA 2 SMA Hang Tuah 4 Surabaya pupils. The Pearson Correlation between learning discipline and parental attention is 0.482 with a significance level of 0.007. It can be said that parental attentiveness and students' learning discipline have a fairly strong link and indicates a substantial correlation between the variables of parental attention and student learning discipline.